Aktivitas Antiplasmodium Daun Sernai (Wedelia Biflora) Berdasarkan Evaluasi Fungsi Ginjal dan Hati pada Mencit yang Diinfeksi dengan Plasmodium berghei - Isa .; Rinidar .; Sugito . (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2012)
This study aimed to determine the antiplasmodial activity of sernai leaves (Wedelia biflora) extractagainst Plasmodium berghei which were infected to mice experimentally using the 4-days suppressive testmethod. The extraction was performed by maceration in three different solvents: ethanol, n-hexane, andethyl acetate. Inoculation of 1x106 P. berghei was performed in 60 Swiss mice intraperitoneally. Theantiplasmodial activity of the ethanol, n-hexana, and ethyl-acetate leaves extract at 4 different doses(100, 80, 60 and 40 mg/kg BW/day, respectively) were tested against P. berghei in vivo for 4 consecutivedays. Animals were given the leaves extracted orally. The negative-control animals were given dimethylsulfoxide diluents (DMSO) and animals in the positive-control were treated with P.berghei + DMSO.Parasitemia status were observed from day 1-4 by thin blood smear from tail and stained with Giemsa.On day 5, levels of urea, creatinine, SGPT and SGOT were measured. The results showed that extract ofsernai leaves using ethanol, n-hexane, and ethyl acetate had the antiplasmodial capacity on P.berghei inmice with effective doses (ED50) of 5.379 mg/kg BW, 25.306 mg/kg BW, and 27.442 mg/kg BW, respectively.The sernai leaves extract had the capability to maintain the liver function but not the kidney function.